Challenges of Digital Transformation of Healthcare Industry in Indonesia - Benedict Sulaiman; Adang Bachtiar (Syntax Idea)
Digital transformation in healthcare is needed to continuously enhance healthcare services in Indonesia, but all the changes happened especially after the Covid-19 pandemic has made many healthcare facilities to face difficulties on prioritizing development and their operational services. The Government thru the Ministry of Health have already defined the direction of where the transformation is expected to be, but to fulfill that expectation will still be a huge challenge for all healthcare facilities, both government and private. This research is intended to bring perspective on the situation and challenges for private healthcare facilities on facing digital transformation. The research method is conducted using cross sectional survey and literature study to several private hospitals. From the results it can be seen that there are various levels of readiness between the hospitals in order to face these challenges, which in some cases still supported by skepticism of the stakeholders on the need for digital transformation. But, at the end it can be concluded that digital transformation is needed and eventually it will come, therefore all hospitals must be ready to face the transformation and changes. All of this are happening for the good of healthcare in Indonesia